Sutureless aortic valve and mitral valve repair in redo cases – really an off-label approach? - Čanádyová, Júlia; Mokráček, Aleš; Kurfirst, Vojtěch (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
Sutureless aortic valve replacement (AVR) was developed as an alternative treatment option to conventional open-heart surgery and transcatheter aortic valve implantation for “gray zone” patients. The need for concurrent mitral valve surgery is generally viewed as a contraindication to sutureless AVR. The purpose of this brief paper is to report our experiences with sutureless valves in patients after previous cardiac procedures with degenerated aortic bioprostheses and concomitant mitral valve disease.